Despeckling - Loizou, Christos P.; Pattichis, Constantinos S. (My University, 2012)
The wide use of ultrasound imaging equipment, including mobile and portable telemedicine ultrasound scanning instruments and computer-aided systems, necessitates the need for better image processing techniques, in order to offer a clearer image to the medical practitioner. This makes the use of efficient despeckle filtering an important task.
Keywords: Synthetic Aperture Radar Image; Anisotropic Diffusion; Speckle Noise; Speckle Reduction; Carotid Artery Bifurcation